Family cluster of multi-drug resistant tuberculosis in Kingdom of Saudi Arabia - Abeer N. Alshukairi; Hanan M. Moalim; Asim Alsaedi; Walaa Y. Almansouri; Mohammed Al-Zahrani; Alaa Aljuaid; Basem M. Alraddadi; Hanan H. Altorkistani; Abdulrahman A. Alrajhi; Sahal A. Al-Hajoj (Elsevier, 2020)
We describe the clinical and genetic characteristics of multi-drug resistant tuberculosis (MDR-TB) in a family cluster in the western region of Kingdom of Saudi Arabia diagnosed between 2012 and 2016. All cases had risk factors for tuberculosis acquisition and they were not household contacts of the index case. Genetic analysis detected both MDR-TB and pre-extensively drug-resistant tuberculosis (pre-XDR TB) strains in the index case and confirmed tuberculosis transmission between two cases. Lack of early diagnosis of MDR-TB by molecular testing and lack of extended contact tracing contributed to the transmission of MDR-TB among this family cluster over four years. Keywords: Multidrug resistant tuberculosis, Family cluster